Cutaneous Inflammatory Malignant Fibrous Histiocytoma Presenting with a Leukemoid Reaction: A Case Report and Review of the Literature - Jorge Hurtado-Cordovi; Boris Avezbakiyev; Marianne Frieri; Lester Freedman; Wondwoosen Gebre (Case Reports in Medicine)
Malignant fibrous histiocytoma (MFH) is the most common sarcoma found in adults. We discuss a case of inflammatory MFH of dermal/epidermal origin presenting with a severe leukemoid reaction (LR). A 60 years old white male presented to hematology/oncology clinic complaining of mild shortness of breath on exertion. Past medical history was remarkable for removal of a left upper extremity necrotic mass 4.4 × 3 × 3 cm. Microscopy of the specimen showed clear surgical margin, and tumor cells restricted to the dermis without lymphovascular invasion. Immunohistochemestry was positive for CD 68 and CD 99. Chest x-ray was negative for metastatic disease. White blood cell count was 109.4 k/mm3 with 24 k/mm3 band neutrophils, and absolute neutrophil count of 69 k/mm3. CT scan of the thorax revealed numerous bilateral pulmonary nodules suspicious for metastasis. Based on these findings patient was diagnosed with metastatic cutaneous IMFH associated with a LR. Following review of medical literature, this appears to be the first reported case of inflammatory cutaneous MFH associated with LR. This histological variant is rare, and carries a poor prognosis. Thus, we would like to emphasize the need for investigating alternative therapies capable of improving the survival of these patients.